リオメーター デ カンソク サレタ 30MHz コンシン ノ セイシツ - 行松, 彰; ユキマツ, アキラ; Yukimatu, Akira (1992)
P(論文) 1989年, 南極あすか観測拠点で30MHzリオメーターの観測を行った。太陽活動が最大級であったこの年, 混信が非常に多く出現した。この混信は規則的な日変化や季節変化を示し, 670km東方の昭和基地でも同様の特性の混信が受信された。この混信は, さらに北半球極域でのリオメーター及び日本での電波観測にも同様に現れており, 地球規模で発生している現象であると考えられる。この混信の出現特性を, 電離層foF_2のデータ, 地磁気活動指数Kp, また太陽黒点数と比較を行った結果, 次のことがわかった。1)リオメーターの混信は主として, 電離層で反射された遠方からの電磁波である。2)混信の出現特性は, 伝搬経路の電離層(特に, F_2層)の状態を反映しており, foF_2とよい相関を示す。3)混信の出現頻度が週末に減少するという出現特性が得られたので, 雑音源は, 自然雑音ではなく, 人工雑音が主であると推定できる。以上により, 混信は単なる不要雑音ではなく, 伝搬経路の電離層や雑音源の情報を含んでおり, また地球の電磁波(特に人工雑音)環境を知る手掛かりともなり得ることがわかった。 In 1989,when the sun was highly active, interference noises were often observed by 30-MHz riometers at Asuka and Syowa Stations in Antarctica. The noises showed a systematic diurnal and seasonal variation. The noises were global phenomena because they were also seen in other riometer data at high and middle latitudes in the northern hemisphere. These noises were investigated in connection with ionospheric foF_2 data, geomagnetic Kp indices and sunspot numbers. The results are summarized as follows; 1) Interference noises consist mainly of ground radio waves reflected by the ionosphere. 2) The interference noise occurrence shows a good correlation with foF_2. 3) The noise intensity shows a tendency of decreasing on weekends, and this feature suggests that the noises are mainly of artificial origins. It is concluded, therefore, that the occurrence feature of the interference noises reflects the condition of the ionosphere, and can be used as an indicator of the global electromagnetic wave environment in HF range. departmental bulletin paper